Gastrointestinal Henoch–Schönlein purpura successfully treated with Mycophenolate Mofetil: Description of 2 case reports - Gicchino, Maria Francesca (Medicine (Baltimore), 2021)
RATIONALE: Henoch–Schönlein Purpura (HSP) is an acute small vessel vasculitis. It is the most common vasculitis in children. In majority of the cases, the disease is self-limited. Relapses can occur, in particular during the first year of the disease. There is no consensus on a specific treatment. The efficacy and safety of steroidal treatment in treating HSP is still controversial. Immunosuppressive treatment of HSP nephritis is used in patients with severe renal involvement (nephrotic range proteinuria and/or progressive renal impairment). The literature on immunosuppressive treatment of severe HSP without kidney involvement is scanty. PATIENTS CONCERNS: We report 2 case reports of 2 adolescents affected from Henoch–Schönlein Purpura and severe gastrointestinal involvement. Both patients presented a poor response to steroids treatment. DIAGNOSES: The diagnosis of HSP was made according to the diagnostic criteria published by European League against Rheumatism and Pediatric Rheumatology European Society in 2006 INTERVENTIONS: In consideration of the recurrence of the Henoch Schönlein Purpura and the gastrointestinal involvement, we decided to start Mycophenolate Mofetil treatment. OUTCOMES: In both patients all clinical manifestations resolved in few days. LESSONS: In our cases of HSP with gastrointestinal involvement Mycophenolate Mofetil treatment has been very effective. This experience teaches us that immunosuppressive agents may be very useful to induce and maintain remission not only in renal involvement, but in all cases of persistent, recurrent, or complicated Henoch Schönlein Purpura in children.